Structural studies on dicopper(II) compounds with catechol oxidase activity - Börzel, Heidi; Comba, Peter; Pritzkow, Hans (Chemical communications, 2001)
The X-ray crystal structures of three low molecular weight models of catechol oxidase with three different coordination modes are reported; and the compound with a bridging catecholate is shown to be the catalytically most active form.
Gesehen am 07.03.2018
Article was first published as an advance article on the web on 15th December 2000